Transparent and flexible coplanar antenna for 5G mobile communication - Rahman, Sahariar; Siddique, Nazmu Shahadat; Haque, Majedul (BRAC University, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.